Circulating adipokines and metabolic setting in differentiated thyroid cancer. Issue 7 (July 2019) - Mele, Chiara; Samà, Maria Teresa; Bisoffi, Alessandro Angelo; Caputo, Marina; Bullara, Valentina; Mai, Stefania; Walker, Gillian Elisabeth; Prodam, Flavia; Marzullo, Paolo; Aimaretti, Gianluca; Pagano, Loredana
Abstract : The associative link relating insulin resistance (IR) and adipokines to the occurrence and phenotype of differentiated thyroid cancer (DTC) is unknown. The aim of this study was to evaluate the relationship between IR and adipokines in DTC patients, as compared with carriers of benign thyroid diseases (BTD) and healthy controls. This observational study enrolled 77 subjects phenotyped as DTC ( N = 30), BTD ( N = 27) and healthy subjects ( N = 20). Each subject underwent preoperative analysis of anthropometric parameters, thyroid function and autoimmunity, insulin resistance (HOMA-IR) and levels of unacylated (UAG) and acylated ghrelin (AG), obestatin, leptin and adiponectin. Multivariate regression models were used to test the predictive role of metabolic correlates on thyroid phenotypes and DTC extension. The three groups showed similar age, gender distribution, smoking habit, BMI and thyroid parameters. Obestatin was significantly higher in DTC group compared to BTD ( P < 0.05) and control subjects ( P < 0.0001). DTC and BTD groups showed higher levels of UAG ( P < 0.01) and AG ( P < 0.05). Leptin levels were comparable between groups, whereas adiponectin levels were lower in DTC compared to BTD group ( P < 0.0001) and controls ( P < 0.01). In parallel, HOMA-IR was higher in DTC than BTD ( P < 0.05) and control group ( P < 0.01). Stepwise multivariable regression analysis showed that obestatin and UAG were independent predictors of DTC ( P = 0.01 for both). In an analysis restricted to the DTC group, obestatin levels were associated with the absence of lymph node metastases ( P < 0.05). Our results highlight a potential association between metabolic setting, circulating adipokines and thyroid cancer phenotype.